Measurement of transverse emittance and coherence of double-gate field emitter array cathodes - Soichiro Tsujino; Prat Das Kanungo; Mahta Monshipouri; Chiwon Lee; R.J. Dwayne Miller (Nature Communications, 2016)
Field emitter arrays are key components for X-ray sources, microwave generators, RF communication and advanced light sources. Tsujinoet al., report double-gate field emitter arrays with competitive beam qualities to the state of the art UV photoexcited cathodes.